2004
DOI: 10.1016/s0022-5193(03)00290-x
|View full text |Cite
|
Sign up to set email alerts
|

A continuous model of biomass size spectra governed by predation and the effects of fishing on them

Abstract: A new time-dependent continuous model of biomass size spectra is developed. In this model, predation is the single process governing the energy flow in the ecosystem, as it causes both growth and mortality. The ratio of predator to prey is assumed to be distributed: predators may feed on a range of prey sizes. Under these assumptions, it is shown that linear size spectra are stationary solutions of the model. Exploited fish communities are simulated by adding fishing mortality to the model: it is found that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(196 citation statements)
references
References 45 publications
6
190
0
Order By: Relevance
“…1). Hence, specific rates of ingestion and mortality are regulated by the concentration of the food source and biomass, respectively, yielding a density-dependent formulation in the case of mortality, as in, for example, Benoit and Rochet (2004). Use of density-dependent terms, through either resource-limited growth or mortality, is an established way of preventing competitive exclusion in model systems (Brown, 1989;Chesson, 2000).…”
Section: Model Structurementioning
confidence: 99%
“…1). Hence, specific rates of ingestion and mortality are regulated by the concentration of the food source and biomass, respectively, yielding a density-dependent formulation in the case of mortality, as in, for example, Benoit and Rochet (2004). Use of density-dependent terms, through either resource-limited growth or mortality, is an established way of preventing competitive exclusion in model systems (Brown, 1989;Chesson, 2000).…”
Section: Model Structurementioning
confidence: 99%
“…Waves of abundance have been observed in previous models Datta et al 2010) when parameter values were chosen that destabilised the steady state distribution. Adding a plankton bloom has a similar effect, as organisms whose feeding range lies within the plankton spectrum are subject to higher growth rates (Benoît and Rochet 2004;Maury et al 2007a). Here it was observed that seasonal forcing via the reproductive process also pushes the system away from the steady state.…”
Section: Discussionmentioning
confidence: 76%
“…Organisms feed upon smaller organisms in both the resource and consumer spectra according to a Gaussian feeding preference function (Table 1, eq. 4), commonly used in modelling predation in marine systems (Benoît and Rochet 2004;Andersen et al 2009;Law et al 2012). Organisms die either from being eaten by larger organisms or from natural causes (this encompasses starvation and natural mortality; see Table 1).…”
Section: Consumer Spectrummentioning
confidence: 99%
“…The size-based models with the lowest parameter demands rely on empirical relationships that link body mass, temperature and biological rates to support parameterization (e.g. Benoît and Rochet, 2004;Blanchard et al, Geosci. Model Dev.…”
Section: Model Classes: Size-or Age-based Models 25mentioning
confidence: 99%